Hubungan Antara Frekuensi Minum Teh, Siklus Dan Lama ‎Menstruasi Dengan Kejadian Anemia Remaja Putri Kelas 7 Di Mtsn 2 Pandeglang Tahun 2022‎: Relationship Between Frequency of Drinking Tea, Menstrual Cycles, and Length with Anemia Incidence of Grade 7 Young Girls at Mtsn 2 Pandeglang in 2022 - Yuliasih (Dohara POAJ, 2022)
Introduction: Observations made at MTSN 2 Pandeglang as many as 15-20 young women consume tea every day in the form of cold and hot drinks. All types of packaged teas and teabags contain tannins derived from tea extracts that can inhibit the absorption of iron nutrients. If drinking tea occurs continuously, it is certainly not good for the health of young women, especially since young women experience menstrual bleeding every month. Based on these problems, it is necessary to conduct research on the relationship between the frequency of drinking tea, cycles, and menstrual length with the incidence of anemia of grade 7 adolescent girls in MTSN 2 Pandeglang. Methods: This study uses a descriptive-analytical method with a Cross-Sectional study design. With a total sample of 59 people, the sampling technique was carried out by purposive sampling. Data analysis was carried out by means of univariate and bivariate analysis using the chi-square test. Results: There is a relationship between the frequency of drinking tea (p-value = 0,000 and OR = 0,030), menstrual cycle (p-value = 0,001 and OR = 0,101), with the incidence of tea drinking in young women and there is no relationship between menstrual length (P-value = 1,000 and OR = 1,367) with the incidence of anemia in adolescent girls grade 7 in MTSN 2 Pandeglang in 2022. Discussion: There is a relationship between the frequency of drinking tea, and the menstrual cycle with the incidence of anemia in young women, and there is no relationship between the length of menstruation and the incidence of anemia in adolescents in grade 7 MTSN 2 Pandeglang 2022.